Pengaruh Kelompok Referensi, Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Ulang Pada Produk Scarlett Whitening - Mega Aulia Rahmi; Moh. Agung Surianto (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
The aim of this research is to find out how the reference group, product quality, and price influence the re-purchase decision on the Scarlett Whitening product. This research is carried out using quantitative research methods that can be understood as methods used to study a particular population or sample, data collection using research instruments, analysis of data of a statistical nature, with the aim of testing the hypothesis that has been established. The sample in this study is 160 people who have used the Scarlett Whitening product. Sampling technique is purposive sampling. The results show that there is an influence between the reference groups, the quality of the product has an impact on the re-purchase decision, and the price also has an effect on the remarketing decision on the Scarlett Whitening product.